A practical guide to biologically relevant molecular simulations with charge scaling for electronic polarization - Duboué-Dijon, E; Javanainen, M; Delcroix, P; Jungwirth, P; Martinez-Seara, H (The Journal of chemical physics, 2020)
Molecular simulations can elucidate atomistic-level mechanisms of key biological processes, which are often hardly accessible to experiment. However, the results of the simulations can only be as trustworthy as the underlying simulation model. In many of these processes, interactions between charged moieties play a critical role. Current empirical force fields tend to overestimate such interactions, often in a dramatic way, when polyvalent ions are involved. The source of this shortcoming is the missing electronic polarization in these models. Given the importance of such biomolecular systems, there is great interest in fixing this deficiency in a computationally inexpensive way without employing explicitly polarizable force fields. Here, we review the electronic continuum correction approach, which accounts for electronic polarization in a mean-field way, focusing on its charge scaling variant. We show that by pragmatically scaling only the charged molecular groups, we qualitatively improve the charge-charge interactions without extra computational costs and benefit from decades of force field development on biomolecular force fields.
Keywords: membránové lipidy; Proteins; DNA; simulace molekulární dynamiky; Humans; lidé; proteiny; RNA; Membrane Lipids; Molecular Dynamics Simulation; Static Electricity; statická elektřina